New data on Albuca crispa (Hyacinthaceae, Ornithogaloideae), an erect-flowered Albuca from South Africa - Martínez-Azorín, Mario; Crespo, Manuel B.; Dold, Anthony P. (Phytotaxa, 2013)
Within the framework of a taxonomic revision of the genus Albuca we here present new data on Albuca crispa, a species described as having undulate-crispulate leaves and white-green nodding flowers, it being included in A. subgen. Falconera section Trianthera (as series Trianthera). After studying both herbarium specimens and living plants from the type locality and other locations, it is clear that the protologue of A. crispa includes remarkable inaccuracies that make the understanding of that species very difficult, and that therefore are in need of correction. Furthermore, the new data would support the transfer of Albuca crispa to A. subgen. Mitrotepalum, a group characterized by the erect flowers and strongly hooded inner tepals. A complete description is presented for this species, and data on morphology, ecology, and distribution are reported. Affinities and divergences with other close allies are also discussed, and evidence is shown to propose amendment of author citation.